Association of age and caries experience among adult population - An institutional study - SUBRAMANIAN, VAISHNAVI SIVAKALI; L. LEELAVATHI,; KUMAR S, ARAVIND (The journal of contemporary issues in business and government, 2021)
Oral health is closely related with general health and people’s quality of life, through affecting their oral functions and social interactions. Dental caries are the major concerns among oral health.The aim of the study is to assess caries experience based on Decayed Missing Filled Teeth Index (DMFT) index among adults patients visiting a private dental college in Chennai. DMFT index was used to evaluate the caries experience. Patient case sheets were reviewed, index scores and age of the patients were collected . 4567 patients were selected for the study and tabulated in excel sheet and statistically analysed using SPSS. Frequency distribution was done using descriptive statistics and Chisquare test was used to analyse the association of caries experience with different age groups. In this study, it was observed that 18-35 year old patients were most prevalent (47.7%) and DMFT scores ranging from 0-7 were maximum with 58.2%. Within the limits of the study, results of the study showed that DMFT score of more than 8 suggesting higher caries experience was prevalent in study participants above 55 years of age. DMFT score of 0-7 was the most prevalent score among 18-35 years and 36-55 years.